2021
DOI: 10.1152/ajpheart.00628.2020
|View full text |Cite
|
Sign up to set email alerts
|

Acute e-cig inhalation impacts vascular health: a study in smoking naïve subjects

Abstract: Objective: This study was designed to investigate the acute effects of non-nicotinized e-cigarette (e-cig) aerosol inhalation in nonsmokers both in terms of blood-based markers of inflammation and oxidative stress and evaluate their association with hemodynamic-metabolic MRI parameters quantifying peripheral vascular reactivity, cerebrovascular reactivity and aortic stiffness. Approach and Results: Thirty-one healthy nonsmokers were subjected to two blood draws and two identical MRI protocols, each one before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…Vaping e-cigarettes (e-cigs) is viewed by many people as benign but a growing literature indicates harmful effects to multiple systems, including cardiovascular effects. [1][2][3][4][5][6][7] Although e-cigarettes have been promoted as cessation aids for adults, this is debatable. 8,9 Young adults who are not accustomed to the effects of nicotine are experimenting, 10,11 leaving them more prone to future cigarette use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaping e-cigarettes (e-cigs) is viewed by many people as benign but a growing literature indicates harmful effects to multiple systems, including cardiovascular effects. [1][2][3][4][5][6][7] Although e-cigarettes have been promoted as cessation aids for adults, this is debatable. 8,9 Young adults who are not accustomed to the effects of nicotine are experimenting, 10,11 leaving them more prone to future cigarette use.…”
Section: Introductionmentioning
confidence: 99%
“…A single vaping session in healthy adults increased endothelial cell signaling and biomarkers correlating with adverse functional vascular changes. 6 Flavorants are another important category of potentially harmful e-liquid components. According to the National Youth Tobacco Survey, 8 out of 10 e-cig users used flavored e-cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…How does ROS exert effects on the circadian rhythm, and how is the pulmonary endothelium affected by this altered amplitude? ROS is well established to upregulate several inflammatory moieties on the pulmonary endothelium; among these is the NLRP3 inflammasome, that we and others have shown to be induced by ROS [17, 37]. We thus reasoned that the alteration of circadian rhythms by ROS could be via NLRP3.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, both in vitro and in vivo studies suggest exposure to ultrafine particles in the aerosol can lead to adverse cardiovascular effects, hemodynamic hyperreactivity, and oxidative stress after a single vaping instance in otherwise naive subjects. 5 Impairment in lung function, reduced innate immunity to pulmonary infections, and increased pulmonary inflammation have also been documented. 6 Longitudinal studies have demonstrated worrisome exposure to known tobacco-related toxicants and associations with elevated risk of incident pulmonary disease.…”
Section: E-cigarette Aerosol Is Not Water Vapormentioning
confidence: 99%
“…Common misunderstandings include overstating the relevance of minute toxicant exposures, heroic projection of cell and animal studies to living humans, misattribution of the effects of decades of smoking to subsequent vaping, mistaking observable physiologic effects for material health risks, asserting gateway effects that are better explained by residual confounding by common liabilities, ignoring reverse causation (vaping to mitigate smoking-related risks), or seeing dual-use as somehow worse than exclusive smoking, when it represents part of a transitional pathway, often for more dependent users. 5,6 Also, critics of tobacco harm reduction rarely acknowledge the failure to reach millions of smokers with the existing toolkit of punitive and stigmatizing tobacco control measures and clinically orientated smoking cessation methods that work better in clinical trials than in the real world. 7 Vaping offers a conceptually different, user-orientated approach.…”
Section: E-cigarette Use Is Common Among Adolescentsmentioning
confidence: 99%